Children’s perception of the visual identity of Belgrade - Bogdanović Bojana (Glasnik Etnografskog Instituta SANU, 2022)
The focus of this paper is a research field that has (until now) remained outside the main academic theoretical frameworks - the question of the visual identity of Belgrade seen (and experienced) from the perspective of children. In methodological terms, the paper relies on the results of field research conducted in March 2021 at the Kneginja Milica (Princess Milica) Primary School in New Belgrade, which included a sample of 60 children from Years 1 to 4. The aim of the paper is to discuss from an anthropological perspective some of the key issues of perceiving the appearance of the capital as a visual entity per se: 1) Which visual markers of Belgrade, in the opinion of children, are key to its visual identity and what are the central points on the symbolic map of the capital?; 2) What is the main symbol of Belgrade and what criteria guide the participating children when selecting this central visual marker?; 3) (To what extent) are individual children’s perceptions of the panorama of the capital compatible with each other and what are the characteristics of the general children’s image of the capital?; 4) (In what way) Is the children’s image of the city in harmony with the ‘official’ image of Belgrade? and 5) Is the child’s perception of the visual identity of the capital the result of direct or indirect urban experience?